2018
DOI: 10.1038/s41598-018-24272-8
|View full text |Cite
|
Sign up to set email alerts
|

Perineuronal Net Protein Neurocan Inhibits NCAM/EphA3 Repellent Signaling in GABAergic Interneurons

Abstract: Perineuronal nets (PNNs) are implicated in closure of critical periods of synaptic plasticity in the brain, but the molecular mechanisms by which PNNs regulate synapse development are obscure. A receptor complex of NCAM and EphA3 mediates postnatal remodeling of inhibitory perisomatic synapses of GABAergic interneurons onto pyramidal cells in the mouse frontal cortex necessary for excitatory/inhibitory balance. Here it is shown that enzymatic removal of PNN glycosaminoglycan chains decreased the density of GAB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 58 publications
0
32
0
Order By: Relevance
“…Genetic studies in humans revealed that the variation of NCAN, a gene encoding PNN component protein neurocan, is a common risk factor for schizophrenia and bipolar disorder (Mühleisen et al, 2012;Oruč et al, 2012;Schultz et al, 2014). Neurocan has also been shown to regulate brain development, dendritic spine remodeling and the function of GABAergic interneurons (Zhou et al, 2001;Mohan et al, 2018;Sullivan et al, 2018). The assembly and function of PNNs are disrupted when these component proteins are hydrolyzed or the structures are destroyed, which could ultimately lead to negative consequences and pathophysiology of neuropsychiatric disorders (Wen et al, 2018;Testa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic studies in humans revealed that the variation of NCAN, a gene encoding PNN component protein neurocan, is a common risk factor for schizophrenia and bipolar disorder (Mühleisen et al, 2012;Oruč et al, 2012;Schultz et al, 2014). Neurocan has also been shown to regulate brain development, dendritic spine remodeling and the function of GABAergic interneurons (Zhou et al, 2001;Mohan et al, 2018;Sullivan et al, 2018). The assembly and function of PNNs are disrupted when these component proteins are hydrolyzed or the structures are destroyed, which could ultimately lead to negative consequences and pathophysiology of neuropsychiatric disorders (Wen et al, 2018;Testa et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…How this SNP influences NCAN RNA and Neurocan protein expression or function and how it relates to neuronal functions remains to be experimentally determined. The Neurocan protein is involved in the regulation of peri‐neuronal nets around (parvalbumin) neurons and it is shown that peri‐neuronal nets are decreased in MS cortical gray matter lesions compared to normal appearing gray matter without a reduction in the number of neurons . This suggests that Neurocan and the stability of peri‐neuronal nets could be associated with cortical demyelination in MS, and could possibly be influenced by the genotype at rs1064395.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were pre-treated with or without Neurocan for 30 min, then stimulated with 3 nM Sema3F-Fc or Fc protein for 30 min. We used a concentration of Neurocan (20 nM) that exceeded the Kd for Neurocan binding to L1-CAM (∼1 nM) ( Friedlander et al, 1994 ; Milev et al, 1998 ), effectively inhibited ephrinA5-induced axon terminal retraction in cortical neuron cultures ( Sullivan et al, 2018 ), and was within the estimated physiological range in rodent brain, which varies with age and region ( Rauch et al, 1992 ; Bhattacharyya et al, 2015 ). Analysis of spine density on apical dendrites of EGFP-labeled neurons showed that Neurocan (20 nM) blocked Sema3F-induced spine retraction, but had no effect on spine density of Fc-treated neurons ( Figures 3A,B ).…”
Section: Resultsmentioning
confidence: 99%
“…NrCAM-Fc protein was adsorbed to ELISA plates that were pre-coated with Protein A, then incubated with Neurocan-AP or AP control protein for 1.5 h. Binding was quantified by colorimetric detection of bound AP using p-nitrophenylphosphate. As a positive control, Neurocan-AP was also assayed for binding to NCAM, a different cell adhesion molecule known to engage Neurocan at its extracellular Ig2 domain ( Sullivan et al, 2018 ). Neurocan-AP bound to NrCAM-Fc to a significantly greater extent than control AP ( Figure 4F ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation